Analisa Perda DKI Jakarta No. 1 Tahun 2012 tentang Rencana Tata Ruang Wilayah 2030 - Mulyana, Momon; Syahamin, Ahmad (HUMANIORUM, 2024)
This research uses the Empirical Juridical Method, examining the legal provisions that apply to implementation in reality. The applicable legal provisions referred to are Regional Regulation Number 1 of 2012 concerning the 2030 Regional Spatial Planning regarding the development of Green Open Space (RTH) for the DKI Jakarta Province Region in the Jagakarsa District, South Jakarta Administrative City. Regarding the problem of how to regulate green open space development in the Jagakarsa District area, are there any obstacles and what are the solutions. The results of this research show that Jagakarsa District is the area that has the largest green open space in the South Jakarta Administrative City area. The distribution of green open space in the Jagakarsa sub-district includes the distribution of green open space (RTH) in the Jagakarsa sub-district including urban forests, setu/lakes, reservoirs/river runoff spaces, reservoirs, interactive parks, environmental parks, road medians, river and canal borders, edges of railway lines. fire, under the electric power transmission network with shade plants, and local ornamental plants. The obstacle faced in the construction and development of green open space is changing the function of land to residential land. As a solution to suppress residential development by enforcing spatial zoning regulations. The role of the DKI Jakarta Regional Government in RTH is to carry out planning, utilization and control of green open space layout. The people of Jagakarsa District really feel the benefits of Green Open Space, clean air, the availability of clean water sources even though in the dry season, the Jagakarsa area is not too badly affected by drought, including floods.